Views of Islam and Human Rights Regarding LGBT Regarding Punishment in Accordance with Islamic Shari'a - Vicki Dwi Purnomo; Ishvi Joenaini Koenti; Andrie Irawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
LGBT people are illegal and the law and the government guarantee freedom of religion, expression, association, assembly and the right to privacy. This research was carried out normatively with the aim of the State being able to exercise civil rights directly before a judge, as well as social rights such as housing, social security, health, education, and workers' rights. In Indonesia, LGBT people also receive human rights protection in the form of health insurance to help them recover from illness. Recognition or legalization of deviant LGBT sexual orientation is not a human rights issue.